Enhancing awareness of breast self-examination and pap smears for early detection of breast and cervical cancer - Meike Rachmawati; Ismawati Ismawati; Mira Dyani Dewi (University of Merdeka Malang, 2024)
Reproductive health problems, especially breast cancer and cervical cancer are the most common cancers diagnosed in women in Indonesia. Currently, several testing methods to detect breast and cervical cancer early, such as breast self-examination (BSE) and pap smears, have been used to reduce cancer risk factors. However, these two methods are still not widely used. Outreach activities have been proven to increase knowledge about the importance of BSE and pap smears in women. This community service program aims to increase knowledge about the causes and symptoms of breast and cervical cancer, as well as early detection using BSE and pap smears. This service activity plan consisted of preparation, implementation, and evaluation stages. The method used consists of delivering interactive material, discussion, and practice. This activity was attended by 38 participants, consisting of women from PKK cadres in the Andir area, Ciroyom District, the majority of whom were over 35 years old. Based on the results of the post-test, this community service activity was successful in increasing participants' knowledge, attitudes, and behavior towards breast and cervical cancer as well as the early detection methods of BSE and pap smears.